2004
DOI: 10.1080/00224490409552244
|View full text |Cite
|
Sign up to set email alerts
|

Pheromonal influences on sociosexual behavior in postmenopausal women

Abstract: To determine whether a putative human sex-attractant pheromone increases specific sociosexual behaviors of postmenopausal women, we tested a chemically synthesized formula derived from research with underarm secretions from heterosexually active, fertile women that was recently tested on young women. Participants (n = 44, mean age = 57 years) were postmenopausal women who volunteered for a double-blind placebo-controlled study designed, to test an odorless pheromone, added to your preferred fragrance, to learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The animal study done by Mornex [13] [16] studied the phenomenon of humans' sociosexual behavior in post-menopausal women which can be enhanced with the help of sex pheromones. The experiment with duration of 6 weeks was conducted with tested chemically produced formula from underarm excretion from sexually active and fertile women participants.…”
Section: Olfactory Cuesmentioning
confidence: 99%
“…The animal study done by Mornex [13] [16] studied the phenomenon of humans' sociosexual behavior in post-menopausal women which can be enhanced with the help of sex pheromones. The experiment with duration of 6 weeks was conducted with tested chemically produced formula from underarm excretion from sexually active and fertile women participants.…”
Section: Olfactory Cuesmentioning
confidence: 99%
“…One reason for this might be the existence of display rules (Ekman, Sorenson, & Friesen, 1969, based on Goffman, 1967) that allow people to strategically display or hide their attraction to potential mates. If we look at the neurochemistry of love, sex-attractant pheromones have been found to influence women’s self-reports of sociosexual behaviors such as petting, kissing, and other displays of affection (McCoy & Pitino, 2002; Rako & Friebely, 2004), but this alleged increase in women’s sexual attractiveness to men has been contested (Hays, 2003). Neuroimaging studies of basic emotions remain contradictory and inconclusive (e.g., Barrett & Wager, 2006; Murphy, Nimmo-Smith, & Lawrence, 2003; Vytal & Hamann, 2010), and most of them exclude the concept of love from their scope, even along with other emotional concepts.…”
Section: Is Love a Basic Emotion?mentioning
confidence: 99%
“…It has not been decidedly demonstrated that the effects of putative pheromones translate to behavior, but one study provided evidence for an effect of androstenol on behavior such that women exposed to androstenol overnight interacted to a higher degree with men the morning after. 26 Studies using a secret mixture of putative pheromones as an additive to perfume have suggested effects on sociosexual behavior such that men with additional male pheromones and women with additional female pheromones report engaging in more sexual activities, 27, 28, 29 although see also ref. 30.…”
Section: Introductionmentioning
confidence: 99%